1984
DOI: 10.1111/j.1532-5415.1984.tb02006.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Hormone Responsiveness and Aging in the Rat: Problems in the Interpretation of Aging Research

Abstract: Fat is a metabolically dynamic tissue. Its metabolism is under the control of several well-characterized hormonal systems. There appear to be changes in the hormonal sensitivity of rat fat with age. No single mechanism has been proved to explain all the changes observed in adipocyte hormonal responsiveness with aging, although it does seem likely that age does have an independent effect on fat metabolism from studies to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…Substantial changes in fat tissue metabolic function occur during aging, with declines in insulin, lipolytic, and fatty acid responsiveness (Bertrand et al , 1980; Yu et al , 1982; Kirkland & Dax, 1984; Yki-Jarvinen et al , 1986; Silver et al , 1993; Gregerman, 1994; Kirkland & Dobson, 1997; Kirkland et al , 2002; Das et al , 2004; Tchkonia et al , 2006a). Together with preadipocyte dysfunction, impairments in ability to accumulate or mobilize lipid with aging reduce the dynamic range over which fat cells can store or release energy or respond to excess systemic lipotoxic fatty acids.…”
Section: Fat Tissuementioning
confidence: 99%
“…Substantial changes in fat tissue metabolic function occur during aging, with declines in insulin, lipolytic, and fatty acid responsiveness (Bertrand et al , 1980; Yu et al , 1982; Kirkland & Dax, 1984; Yki-Jarvinen et al , 1986; Silver et al , 1993; Gregerman, 1994; Kirkland & Dobson, 1997; Kirkland et al , 2002; Das et al , 2004; Tchkonia et al , 2006a). Together with preadipocyte dysfunction, impairments in ability to accumulate or mobilize lipid with aging reduce the dynamic range over which fat cells can store or release energy or respond to excess systemic lipotoxic fatty acids.…”
Section: Fat Tissuementioning
confidence: 99%
“…It has been appreciated that fat tissue is regionally heterogeneous with respect to the content of stem cells and metabolic function. 1,2 From the aspect of cell sources of regenerative medicine, the contents and characterization of adiposederived stem cells (ADSCs) isolated from different depots of rats and humans have been reported. [3][4][5][6] Fraser et al 3 reported that adipose tissue from hip yielded 2.3-fold more ADSCs than abdomen, and the cells from hip had more potency to differentiate into osteogenic lineages, suggesting the importance of selection of the harvest depot if one considers to use adipose tissue as a cell sources for regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The amount and distribution of fat are important factors that influence the meat quality in the beef industry [1], [2]. For several decades, it has been known that adipose tissues are regionally heterogeneous with respect to metabolic activities and functions [3][5]. Evidences showed that the numerous biological and genetic differences among adipose tissues depend on their anatomical locations [6][8].…”
Section: Introductionmentioning
confidence: 99%